Therapeutic Trial of Modified Levofloxacin (MOLVX) Against Induced Colorectal Aberrant Crypt Foci (Precancerous Tissue) in Mice - K Tarab, Mohammed; M AL-Rekabi, Falah (The Iraqi Journal of Veterinary Medicine, 2022)
Colorectal cancer ranks as the third most commonly diagnosed cancer and the second leading cause of cancer-related deaths globally. ‎Fluoroquinolones, particularly Levofloxacin, have garnered interest for their potential anti-cancer effects, primarily due to their high affinity ‎for metallic ions like copper. This affinity enhances their spectrum of activity and enables greater interaction with DNA in cancer cells, ‎thereby inhibiting proliferation. Building on our prior work, where we synthesized copper-modified Levofloxacin (MOLVX), this study ‎explores its therapeutic potential in treating precancerous colorectal lesions, known as Aberrant Crypt Foci (ACF), in a murine model. Sixty ‎female Balb-C mice were randomized into six groups (n=10 per group). The first group served as a negative control and received no treatment. ‎The remaining groups were administered azoxymethane (AOM) at 10 mg/kg body weight (BW) twice weekly to induce ACF. Among these, the ‎second group acted as a positive control and received no further treatment. The third group was intraperitoneally administered doxorubicin at ‎‎16.2 mg/kg BW once a week for four weeks. The fourth group was treated with Levofloxacin at 25 mg/kg BW via oral lavage daily for four ‎weeks. The final two groups received daily oral lavage treatments of MOLVX at doses of 5 mg/kg and 2.5 mg/kg BW for four weeks, ‎respectively. Histopathological analysis of ACF tissues, stained with hematoxylin and eosin, revealed a statistically significant reduction ‎‎(P<0.05) in ACF count among groups treated with MOLVX, doxorubicin, and Levofloxacin, compared to the positive control. Additionally, both ‎MOLVX-treated groups showed a significant decrease (P<0.05) in proliferating cellular antigen (PCNA) levels. In conclusion, both MOLVX ‎dosages (2.5 mg/kg and 5 mg/kg BW) demonstrated promising therapeutic efficacy against precancerous colorectal lesions in mice. However, ‎the 5 mg/kg BW dose appeared to be more potent.